DEPA classification: a proposal for standardising PRP use and a retrospective application of available devices. Issue 1 (4th February 2016) - Magalon, J; Chateau, A L; Bertrand, B; Louis, M L; Silvestre, A; Giraudo, L; Veran, J; Sabatier, F
Abstract : Background/aim: Significant biological differences in platelet-rich plasma (PRP) preparations have been highlighted and could explain the large variability in the clinical benefit of PRP reported in the literature. The scientific community now recommends the use of classification for PRP injection; however, these classifications are focused on platelet and leucocyte concentrations. This presents the disadvantages of (1) not taking into account the final volume of the preparation; (2) omitting the presence of red blood cells in PRP and (3) not assessing the efficiency of production. Methods: On the basis of standards classically used in the Cell Therapy field, we propose the DEPA (Dose of injected platelets, Efficiency of production, Purity of the PRP, Activation of the PRP) classification to extend the characterisation of the injected PRP preparation. We retrospectively applied this classification on 20 PRP preparations for which biological characteristics were available in the literature. Results: Dose of injected platelets varies from 0.21 to 5.43 billion, corresponding to a 25-fold increase. Only a Magellan device was able to obtain an A score for this parameter. Assessments of the efficiency of production reveal that no device is able to recover more than 90% of platelets from the blood. Purity of the preparation reveals that a majority of the preparations are contaminated by red blood cells as only three devices reach an A score for this parameter, corresponding to a percentage of platelets compared with red blood cells and leucocytes over 90%. Conclusions: These findings should provide significant help to clinicians in selecting a system that meets their specific needs for a given indication.